Pharmacy Alumni Views on Communication with their College after Graduation: A Cross-Sectional Survey: Pharmaceutical Science-Pharmacy - Tulbah, Alaa; E. Ainousah, Bayan; Fairaq, Arwa; Alhindi, Yosra (International Journal of Life Science and Pharma Research, 2022)
As the growing number of pharmacy students increases in Saudi Arabia, here in the western region Umm Al-Qura University, we found the need of investigating the views and preferences of pharmacy graduates towards their future careers and communication with their college. The main aim and objective of our research is to examine the perspectives of intern students, employers, and alumni regarding communication with their college. This is a cross-sectional study with a total of 201 graduates between 2009 and 2020 from the college of Pharmacy, Umm Al-Qura University, who completed the questionnaire from January 2019 to January 2021. The study showed that most of the applicants agreed with the convenience and meaningful effect of the internship and summer training on the occupied jobs. This agreement was in both Pharm-D and B-pharm programs and in both male and female.